(3 + 2√2)^{(x2 - 3)} be y.
Now, (3 + 2√2)^{(x2 - 3)} = ()^{(x2 - 3)} = ()^{(x2 - 3)} = ()^{(x2 - 3)} =
∴ Equation can be written as:-
y + = b
y^{2} + 1 = by
y^{2} – by + 1 = 0
The roots of the equation are:-
y =
=
= 3 ± 2√2
∴ Case 1 = (3 + 2√2)^{(x2 - 3)} = 3+2√2
=) x^{2} – 3 = 1
=) x^{2} = 4 =) x = ± 2
Case 2 = (3 + 2√2)^{(x2 - 3)} = 3-2√2
=) x^{2} – 3 = -1
=) x^{2} = 2 =) x = ± √2
Correct Answer: All of the above
All features of the online course, including the classes, discussion board, quizes and more, on a mobile platform.
Download videos onto your mobile so you can learn on the fly, even when the network gets choppy!